Analisis Komparatif Hukum Nasional–Hukum Islam Pada Pengangkatan Anak Dalam Putusan No. 438/PDT.P/2023/PA.JU - Nasution, Jumanah; Siregar, Ramadhan Syahmedi (Indonesia, 2024)
This research highlights academic problems in the form of child adoption which must comply with Indonesian law, including in Decision no. 438/PDT.P/2023/PA.JU. The aim of the research is to assess the suitability of the decision with the Civil Code and KHI. The research method used is qualitative research, a type of library study. Primary data was obtained from Decision No. 438/PDT.P/2023/PA.JU, Civil Code and Compilation of Islamic Law (KHI) regarding child adoption, while secondary data comes from various supporting literature, including books and journals and the results of scientific research. All data obtained was analyzed causally comparative and causal descriptive in order to achieve research objectives. The research results show that decision no. 438/PDT.P/2023/PA.JU complies with the provisions of KHI, Civil Code, and PP No. 54 of 2007 concerning adoption of children. This is because the decision takes into account the best interests of the child, involves the consent of the biological parents, recommendations from social services and strict verification by the court so that the adoption of the child by the applicant complies with regulations, ensuring that the child's rights are protected and their welfare is guaranteed.